Comparison of numerical modelling approaches for the residual burst pressure of thick type IV composite overwrapped pressure vessels related to low-velocity impact. (October 2022) - Czichos, R.; Bergmann, T.; Moldering, F.; Middendorf, P.
Abstract: Residual burst pressure of thick composite pressure vessels related to low-velocity impacts is investigated numerically. Different modelling approaches from simple shell to complex 3D solid models with multiple delamination interfaces are compared. Burst pressure without impact is used to estimate the quality of the different approaches, whereby the best experimental agreement is observed for the complex 3D solid model. For the low-velocity impact, two locations are investigated, one in the cylindrical and another in the dome region. The influence of additional delamination interfaces is investigated and significantly affects the resulting reaction force and intrusion depth of the impactor. Furthermore, it is shown that the consideration of just one interface gives similar results as the shell model, but both models still result in a too stiff behaviour. Only the consideration of multiple interfaces leads to good results compared to the experiments in terms of impact and residual burst pressure behaviour. For the impact on the dome area as well as the shell model, excessive element deletion is observed, leading to problems for the subsequent pressurising, which requires further investigation. Highlights: Numerical comparison for modelling thick composite pressure vessels. Low velocity impact on cylindrical and dome area. Shell models are unable to capture correct stress distribution through thickness. Solid models with multiple interfaces need to be used for burst and residual burst pressure after impact.